2007
DOI: 10.1097/gme.0b013e31802b6cb1
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous androgen levels and cardiovascular risk profile in women across the adult life span

Abstract: Endogenous testosterone and the adrenal preandrogens per se are not significant independent determinants of circulating high-sensitivity CRP or lipoprotein lipids. Our analyses provide further support for the independent predictive value of low SHBG levels for CVD risk profile and an independent contribution of the menopausal transition to the determination of low-density lipoprotein cholesterol and triglycerides.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(39 citation statements)
references
References 37 publications
1
38
0
Order By: Relevance
“…Yasui et al 60 found that associations of SHBG with HDL-C and triglycerides were no longer significant after controlling for BMI. In another study, a similar lack of independence was observed for the association with HDL-C. 64 Conversely, in several studies associations between SHBG and triglycerides 5,6,55,64 and HDL-C 5,17 persisted after adjustment for BMI or WHR. In the study of Lambrinoudaki et al, 5 associations of TT and FT with triglycerides and HDL-C were not explained by BMI.…”
Section: Lipid Profilementioning
confidence: 67%
“…Yasui et al 60 found that associations of SHBG with HDL-C and triglycerides were no longer significant after controlling for BMI. In another study, a similar lack of independence was observed for the association with HDL-C. 64 Conversely, in several studies associations between SHBG and triglycerides 5,6,55,64 and HDL-C 5,17 persisted after adjustment for BMI or WHR. In the study of Lambrinoudaki et al, 5 associations of TT and FT with triglycerides and HDL-C were not explained by BMI.…”
Section: Lipid Profilementioning
confidence: 67%
“…51 Other investigators have suggested that SHBG, not androgen production, is the primary marker of insulin resistance, and that the SHBG level has independent predictive power for cardiovascular risk for women. 83 Both of these studies were cross-sectional but prospective studies, including a nested case-controlled study, showed weak trends toward increased risk of CVD among women having higher androgen/estrogen ratios: among postmenopausal women not taking any hormone therapy, women with lower SHBG or with high free androgen indexes were at increased risk of CVD events. 84 Basic science 85 and clinical 86 data suggest that exogenous testosterone administration to women may promote abdominal fat deposition.…”
Section: Systemic Estrogenmentioning
confidence: 99%
“…(26) Bell RJ et al study showed a low SHBG levels detect CVS risk profile with a significant association for HDL-C (p < 0.01) and TG (p < 0.01) in both premenopausal and postmenopausal women, but not significant in this study with HDL-C (r= -0.003, p= NS) and TG (r= -0.045, p= NS). (27) The correlation of DHEA with age (r= -0.197, p < 0.05) was negative in accordance of fact that DHEA in women declines in a linear fashion with age. (24) The pool of androgens in women decreases progressively from the age of 30 years in parallel with the decrease in serum concentration of DHEA.…”
Section: Discussionmentioning
confidence: 81%